Análise do desenvolvimento de habilidades gerenciais através do esporte universitário na UFOPA, Campus Alenquer - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study analyzes how university sports practice at UFOPA's Alenquer campus contributes to the development of managerial competencies among students. The research used a qualitative approach, applying semi-structured questionnaires with open-ended questions and field notes. Results showed that participation in sports activities enhances skills such as leadership, teamwork, planning, communication, and conflict resolution. Despite structural and institutional challenges, students adopt autonomous and collaborative strategies to ensure sports participation. The study concludes that university sports function as a space for comprehensive education and student retention polic
Keywords: Esporte universitário; Competências gerenciais; Gestão participativa; Permanência estudantil; Formação integral; CNPQ::CIÊNCIAS HUMANAS